Effects of Tongluo Zhitong formula on synovial fibroblast proliferation in human knee osteoarthritis - Li-Li Yang; Qing-Fu Wang; Xiao-Fang Ding; Huan Liang (Heliyon)
Objective: We aimed to investigate the effects of Tongluo Zhitong formula on synovial fibroblast proliferation in human knee osteoarthritis (KOA). Methods: Discarded synovial tissue collected from patients undergoing total knee arthroplasty at our hospital was digested with type I collagenase. Primary culture was performed on three to four generations of fibroblasts, which were treated with high, medium, and low concentrations of Tongluo Zhitong formula. The KOA synoviocyte proliferation level was detected through applying the methyl-thiazol-tetrazolium (MTT) method, and cell morphology at each concentration was observed under inverted microscopy. Results: Significant differences were observed between three concentration categories and a blank control (p < 0.05). MTT assay test results indicated that as the Tongluo Zhitong formula concentration decreased, the absorbance/optical density value of KOA synovial cells at 490 nm increased. As the concentration increased, a positive inhibition rate was observed in the high concentration category. As the concentration decreased, a negative inhibition rate was observed in the low concentration category. In phase S, the Tongluo Zhitong formula inhibited deoxyribonucleic acid replication, which became more pronounced at increasing concentrations. In the G2 phase, the proportion of cells in the mitotic preparation phase did not change in the low concentration category (p > 0.05). The proportion of cells in the mitotic preparation phase significantly increased in the high and medium concentration categories (p < 0.05). Conclusion: High and medium concentrations of Tongluo Zhitong formula inhibited cell proliferation; therefore, the formula had an inhibitory effect on the cell cycle of synovial fibroblasts.